Eruptions at Lone Star Geyser, Yellowstone National Park, USA: 1. Energetics and eruption dynamics. Issue 8 (13th August 2013) - Karlstrom, Leif; Hurwitz, Shaul; Sohn, Robert; Vandemeulebrouck, Jean; Murphy, Fred; Rudolph, Maxwell L.; Johnston, Malcolm J. S.; Manga, Michael; McCleskey, R. Blaine
Abstract : [1] Geysers provide a natural laboratory to study multiphase eruptive processes. We present results from a 4 day experiment at Lone Star Geyser in Yellowstone National Park, USA. We simultaneously measured water discharge, acoustic emissions, infrared intensity, and visible and infrared video to quantify the energetics and dynamics of eruptions, occurring approximately every 3 h. We define four phases in the eruption cycle (1) a 28±3 min phase with liquid and steam fountaining, with maximum jet velocities of 16–28 m s −1, steam mass fraction of less than ∼0.01. Intermittently choked flow and flow oscillations with periods increasing from 20 to 40 s are coincident with a decrease in jet velocity and an increase of steam fraction; (2) a 26±8 min posteruption relaxation phase with no discharge from the vent, infrared (IR), and acoustic power oscillations gliding between 30 and 40 s; (3) a 59±13 min recharge period during which the geyser is quiescent and progressively refills, and (4) a 69±14 min preplay period characterized by a series of 5–10 min long pulses of steam, small volumes of liquid water discharge, and 50–70 s flow oscillations. The erupted waters ascend from a 160–170°C reservoir, and the volume discharged during the entire eruptive cycle is 20.8±4.1 m 3 . Assuming isentropic expansion, we calculate a heat output from the geyser of 1.4–1.5 MW, which is <0.1 % of the total heat output from Yellowstone Caldera. Key Points: Lone Star geyser has a 4 phase eruptive cycle Choked flow from an overpressured vent occurs during the main eruptive phase Total heat output during an eruptive cycle is 1.4‐1.5 MW